Modified Predictive Torque Control for Balancing Three-Level NPC Inverter-fed Permanent Magnet Synchronous Motor - Hakami, Samer Saleh; Lee, Kyo Beum (2022 International Power Electronics Conference, IPEC-Himeji 2022-ECCE Asia, 2022)
This paper proposes a simple yet effective method to reduce torque ripples of permanent magnet synchronous motor (PMSM) under predictive torque control (PTC). The conventional PTC has been proposed for two-level voltage source inverter (VSI)-fed PMSM drives to reduce torque ripples by restricting the applied voltage vector duty-cycle to 0.7. It is obvious that reducing the duty-cycle of the voltage vector can lead to torque ripple reduction. However, when applying the conventional PTC for PMSM-fed three-level VSI, the system performance is deteriorated due to the applied voltage vector duty-cycle restriction. In addition, small voltage vectors are not selected due to this restriction, which results in unbalanced DC-link capacitors voltages. Therefore, the proposed modified PTC is selecting the small voltage vector for balancing the DC-link capacitors voltages as well as minimizing the torque ripples especially in low-speed operation of the PMSM. The effectiveness of the proposed modified PTC for PMSM-fed three-level VSI is verified through simulation results.
Keywords: Duty-cycle; Neutral point balancing; Neutral-point clamped inverters; Permanent Magnet Synchronous Motor; Permanet magnet synchrnoi motor; Predictive torque controls; Three-level neutral point clamped; Three-level neutral-point-clamped inverte; Torque ripples; Voltage vectors; Neutral-point balancing; permanet magnet synchrnous motor; predictive torque control; three-level neutral-point-clamped inverter